Clinical correlates of charcot–marie–tooth disease in patients with pes cavus deformities. Issue 4 (5th March 2013) - Karakis, Ioannis; Gregas, Matt; Darras, Basil T.; Kang, Peter B.; Royden Jones, H.
<x xml:space="preserve">Abstract</x> Introduction: Given its association with Charcot–Marie–Tooth disease (CMT), pes cavus is a common reason for referral to a neurologist. We investigated clinical features that may predict CMT in children with pes cavus. Methods: In this study we retrospectively reviewed pes cavus patients referred to Boston Children's Hospital in the past 20 years. Patients were categorized as idiopathic or CMT, based on EMG/genetic testing, and their clinical features were compared. Results: Of the 70 patients studied, 33 had idiopathic pes cavus, and 37 had genetically confirmed CMT. Symptoms of weakness, unsteady gait, family history of pes cavus and CMT, and signs of sensory deficits, distal atrophy and weakness, absent ankle jerks, and gait abnormalities were associated with CMT. Conclusions: In children with pes cavus, certain clinical features can predict CMT and assist in selection of patients for further, potentially uncomfortable (EMG) and expensive (genetic) confirmatory investigations. Muscle Nerve, 2013